OP0049 A Genetic Variant in the Region of MMP-9 is Associated with Serum Levels and Progression of Joint Damage in Rheumatoid Arthritis. (23rd January 2014) - De Rooy, D.; Zhernakova, A.; Tsonaka, R.; Willemze, A.; Kurreeman, F.; Trynka, G.; van Toorn, L.; Toes, R.; Huizinga, T.; Houwing-Duistermaat, J.; Gregersen, P.; van der Helm-van Mil, A.
Abstract : Background: The severity of joint destruction is highly variable between Rheumatoid Arthritis (RA) patients. The majority of its heritability is still unexplained. Several auto-immune diseases share genetic risk variants that may also influence disease progression. Objectives: We aimed to identify genetic risk factors for the severity of joint damage in RA by studying genetic susceptibility loci of several auto-immune diseases. Methods: In phase-1, 3143 sets of X-rays of 646 Dutch RA-patients taken over 7-years (Sharp-van der Heijde (SHS) scored) were studied. Genotyping was done by Immunochip. Associations of SNPs with MAF >0.01 and joint destruction were analyzed. In phase-2, 686 North-American RA-patients with 926 SHS-scored X-rays over 15 years of follow-up were evaluated. In both phases multiple testing corrections were done for the number of uncorrelated SNPs; the thresholds for significance were p<1.1x10 -6 and p<0.0036. MMP-9 levels were measured with ELISA in baseline serum samples. Results: In phase-1, 109 SNPs associated significantly with joint destruction (p<1.1x10 -6 ). Of these, 76 were located in the HLA-region; the 33 non-HLA variants were studied in phase-2. Here two variants were associated with the severity of joint destruction: rs451066 on chromosome 14 (p=0.002, MAF=0.20) and rs11908352 on chromosome 20 (p=0.002, MAF=0.21). Rs11908352 is located near the gene encoding Matrix Metalloproteinase-9 (MMP-9). Serum levels of MMP-9 were significantly associated with the rs11908352 genotypes (p=0.007). Conclusions: These data indicate that two loci that confer risk to other autoimmune diseases also affect the severity of joint destruction in RA. Rs11908352 may influence joint destruction via MMP-9 production. Acknowledgements: This work has been supported by grants from the Dutch Arthritis Foundation (Reumafonds) and the Dutch organization of Health research and development (Zon-MW). The authors also would like to acknowledge the RACI study group. The Immunochip analyses were supported by BBMRI-NL. Disclosure of Interest: None Declared